ReFocus The Films of Amy Heckerling - Smith, Frances (Edinburgh University Press, 2022)
A collection of interdisciplinary essays, collected for the first time, on the work of filmmaker and screenwriter Amy HeckerlingClueless and Fast Times at Ridgemont High are affectionately regarded as key foundations of the modern Hollywood teen movie. However, the director and screenwriter for these films, Amy Heckerling, is far from a household name, despite the major influence she has had on contemporary US cinema.The first book-length study of her films, ReFocus: The Films of Amy Heckerling brings together a collection of original essays from a wide range of critical perspectives, aiming to recuperate Heckerling's place as a distinctive female voice in the contemporary Hollywood landscape. Divided into four sections, each examining a distinctive aspect of Heckerling's work, the volume draws on research from applied linguistics and audience studies, as well as from aspects of gender and film studies. Questions of gender, genre and identity, as well as the role of women in Hollywood and the implications of Heckerling's recent turn to television, are all considered in a volume that aims to refocus on the films and influence of this distinctive American director
Description based on online resource; title from PDF title page (publisher's Web site, viewed 02. Mrz 2022)
Keywords: Film, Media & Cultural Studies; PERFORMING ARTS / Film & Video / Direction & Production; Motion pictures, American